2021
DOI: 10.3390/nu13051516
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory and Immunomodulatory Properties of Fermented Plant Foods

Abstract: Fermented plant foods are gaining wide interest worldwide as healthy foods due to their unique sensory features and their health-promoting potentials, such as antiobesity, antidiabetic, antihypertensive, and anticarcinogenic activities. Many fermented foods are a rich source of nutrients, phytochemicals, bioactive compounds, and probiotic microbes. The excellent biological activities of these functional foods, such as anti-inflammatory and immunomodulatory functions, are widely attributable to their high antio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
84
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(90 citation statements)
references
References 189 publications
(266 reference statements)
3
84
0
3
Order By: Relevance
“…Mounting evidence supports the idea that healthy eating habits can control and reduce many epithelial cancers, including breast cancer [ 9 , 10 ]. In this sense, natural products such as probiotics, polyphenols, and fermented plant foods are known for their anti-inflammatory effects [ 11 , 12 , 13 ] and may control neoplasia [ 14 ]. Blueberries are a well-known source of antioxidants and polyphenols [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mounting evidence supports the idea that healthy eating habits can control and reduce many epithelial cancers, including breast cancer [ 9 , 10 ]. In this sense, natural products such as probiotics, polyphenols, and fermented plant foods are known for their anti-inflammatory effects [ 11 , 12 , 13 ] and may control neoplasia [ 14 ]. Blueberries are a well-known source of antioxidants and polyphenols [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Blueberries are a well-known source of antioxidants and polyphenols [ 15 ]. Polyphenols found in blueberries are shown to reduce inflammation, oxidative stress [ 12 ], and metastasis [ 16 ], while promoting apoptosis in cancer cells [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of studies have confirmed that NK has many beneficial effects on cardiovascular health. NK has potent antithrombotic [9], antihypertensive [10], anti-atherosclerotic, lipid-lowering [11], and neuroprotective [12] activities. Moreover, it has been reported that the ether extracts of rice bran subjected to fermentation with B. natto show good antioxidant activity [13].…”
Section: Introductionmentioning
confidence: 99%
“…Low-grade inflammation induced and caused by persistent microbes is challenging because systemic antibiotics or local antiseptics may be used only for a limited time, and they abolish the normal microbiome alongside the pathogens. Natural products, and especially fermented plant foods, may eventually offer an alternative approach to novel anti-inflammatory and immunomodulatory pathways for controlling oral health [25].…”
Section: Special Features In Microbe/host Interactions In the Oral Environmentmentioning
confidence: 99%